(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Job satisfaction is a positive emotion or feeling of pleasure resulting from an employee’s evaluation of work factors or work experience. Several factors that affect job satisfaction must be considered so that employees have high job satisfaction. The purpose of this study was to determine the effect of job insecurity and work ethic on employee job satisfaction. This research was conducted at Keripik Biru Kesiman UMKM. The number of samples taken was 31, using the saturated sample method. The analysis techniques used are validity testing, reliability testing, the classical assumption test, multiple linear regression, the coefficient of determination, the t test, and the F test. The results show that job insecurity has a significant negative effect on job satisfaction, work ethic has a significant positive effect on job satisfaction, and both job insecurity and work ethic have a significant influence on job satisfaction. The results of this study indicate that the influence of the independent variables on job satisfaction is 67.8%. It is hoped that Keripik Biru Kesiman will always improve the comfort of the work environment and provide supporting facilities and infrastructure to increase employee job satisfaction